High pressure processing and heat sterilization of kale: Impact on extractability, antioxidant capacity and storability of carotenoids and vitamin E. Issue 4 (17th June 2022) - Schmidt, Mario; Hopfhauer, Sofia; Schwarzenbolz, Uwe; Böhm, Volker
Abstract: Food process engineering represents a rapidly evolving discipline traditionally focussing on thermal treatments including objectives such as preservation and stabilization. Innovative and gentle preservation techniques such as high‐pressure processing (HPP) may potentially improve or replace conventional methods by enhancing nutritional and health aspects, flavor and taste, sustainability, and more consumer‐targeted, minimally processed food items. As information about the impact of HPP (600 MPa, 5–40 min) on lipophilic food ingredients (e.g., carotenoids, vitamin E) in kale is limited, a comparison to heat sterilization (20 min, 121°C) may result in new insights related to lipophilic, antioxidant capacity (L‐AOC), extractability and storage stability (8 weeks, 5°C). HPP of chopped kale resulted in significantly increased ( p  < 0.05) total carotenoid and chlorophyll contents in contrast to declined concentrations of vitamin E. Significantly decreased extractabilities were observed for total carotenoids and chlorophylls in heat sterilized kale, showing no significant change ( p  > 0.05) in vitamin E content. Moreover, 2 months of storage of HP‐treated kale resulted in a major loss of vitamin E and total carotenoid contents compared to thermally treated samples. Elevated α‐tocopherol equivalent antioxidant capacities (αTEAC) and lipophilic oxygen radical antioxidant capacities (L‐ORAC) correlated with an increased pressure holding time. Abstract : High‐pressure processing (HPP) represents an alternative and gentle preservation method for a wide range of food items. In this study, a comparison of conventional heat sterilization and HPP with varying holding times at 600 MPa provides new insights related to impacts on storability, extractability and antioxidant capacity of lipophilic food ingredients in kale.